Spatial and Temporal Characteristics of Demersal Assemblages in Sığacık Bay, Central Aegean Sea, Turkey - Hakkı DERELİ (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2021)
This study aimed to determine the spatial and temporal variation of species diversity and CPUE in trawl fisheries in the Central Aegean Sea (Sığacık Bay). The study also aimed to evaluate changes in some biometric parameters (mean and frequency of length) depending on the season and depth for three important commercial species (Parapenaeus longirostris, Nephrops norvegicus and Illex coindetii). Monthly trawl samplings were carried out in three depth strata (0-200; 201-400 and 401-600 m) between May 2008 - April 2009. A total of 111 species were identified including 74 Osteichthyes, 13 Chondrichthyes, 18 Cephalopods and 6 Crustaceans. The highest species diversity and catch per unit effort (CPUE) values were obtained at 201-400 m strata. Among these, Osteichthyes had the highest frequency and CPUE values in all strata and seasons. Summer was the season with the highest CPUE in all groups followed by a decrease until winter due to openning of trawl fisheries in the Autumn. The mean carapace length of P. longirostris, the target species in Sığacık Bay trawl fisheries, increased with depth and this species was more abundant at the 201-400 m strata.